2009
DOI: 10.1158/1078-0432.ccr-09-1296
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and Clinical Studies of Gene Therapy with Recombinant Human Adenovirus-p53 Injection for Oral Leukoplakia

Abstract: Purpose: Oral leukoplakia is a well-recognized precancerous lesion of squamous cell carcinoma. When accompanied with abnormal p53 expression, it suffered a higher risk of canceration. The present study was carried out to test whether the recombinant human adenovirus-p53 could introduce wild-type p53 gene to oral leukoplakia cells and induce cell cycle arrest and apoptosis. Experimental Design: We select p53(-) oral dysplastic keratinocyte POE-9n, to observe the growth inhibition, cell cycle change, apoptosis-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 41 publications
0
42
0
1
Order By: Relevance
“…In the second study, Li et al evaluated 22 patients who received intralesional rAd-p53 (5 doses over 2 weeks) for OLK. 18 Mild adverse events were observed, including transient fever in 7 (32%) patients and flu-like symptoms in 2 (9%) patients. Patients were followed for 24 months, and over this time, 5 (23%) had complete regression, 11 (50%) had decreased size of lesions, 4 (18%) had no improvement, and 2 (9%) progressed to invasive squamous cell carcinoma.…”
Section: Adenoviral P53 Gene Therapymentioning
confidence: 97%
“…In the second study, Li et al evaluated 22 patients who received intralesional rAd-p53 (5 doses over 2 weeks) for OLK. 18 Mild adverse events were observed, including transient fever in 7 (32%) patients and flu-like symptoms in 2 (9%) patients. Patients were followed for 24 months, and over this time, 5 (23%) had complete regression, 11 (50%) had decreased size of lesions, 4 (18%) had no improvement, and 2 (9%) progressed to invasive squamous cell carcinoma.…”
Section: Adenoviral P53 Gene Therapymentioning
confidence: 97%
“…More recent efforts elucidated combination therapies of gendicine and epirubicin hydrochlorid (EPI) in gastric cancer [123], and combinatorial Ad-p53 and radiation regimens for patient diagnosed with advanced nasopharyngeal carcinomas [124]. These and addition studies assessing intraepithelial injections of Ad-p53 for the treatment of oral leukoplakia, a precancerous lesion of squamous cell carcinomas [125], and bronchoalveolar lavage of Ad-p53 in patients with bronchioalveolar cell lung carcinoma [126], pointed to tumor inhibitory effects of Ad-p53, in particular in combination with chemo- and radiation therapy, and warrant further, in-depth clinical assessment. Additional efforts have been directed toward the characterization of more advanced vector systems [127], most importantly of oncolytic, conditionally replicating adenoviruses (CRAs) that only replicate in p53-dysfunctional tumor cells [128130].…”
Section: Targeting P53 Signaling For Cancer Therapymentioning
confidence: 99%
“…The dosages in the previous clinical trials of rAd-p53 varied dramatically, from 1–4 × 1012 viral particles per site [8,22,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which were calculated based on the tumor sizes, the medical direction, and the researchers’ personal experiences. Li et al reported that when the MOI was 100, rAd-p53 infection could effectively introduce an exogenous p53 gene into POE-9n cells, and decrease the toxicity and side effects of the adenovirus [62]. Based on the differences in the cells of the solid cancer from various organs, preclinical research on the effective infection titer for gene therapy should be conducted before the clinical trials.…”
Section: Clinical Issues and Experiences Of Gene Therapymentioning
confidence: 99%